Causality Relationship between Electric Power Consumption and Economic Growth in Malaysia and Thailand: ARDL Bound Testing Approach - Tanattrin Bunnag (International Journal of Energy Economics and Policy, 2022)
This paper examined the causal relationships between per capita electric power consumption and economic growth per capita in Malaysia and Thailand. The data used in this study was the yearly data from 1971 to 2014. The ARDL and Granger causality approaches were employed. Overall, the empirical results showed that it had established a long-run relationship between electric power consumption and economic growth. Moreover, the Granger causality approach recognized a one-way causal direction flowing from economic growth to electric power consumption in Malaysia. However, for Thailand, empirical results had no long-run relationship between electric power consumption and economic growth. Therefore, the Granger causality approach had recognized no way of causal direction flowing from electric power consumption to economic growth. Finally, the empirical results of this study provided policymakers a better understanding of energy consumption and economic growth nexus to formulate energy policy in Malaysia and Thailand. In addition, the government of Malaysia should consider the economic situation when implementing the relevant energy policies.